Analisis Kajian As-Saj’u dalam Surah Al Ghasiyah - Muhammad Fadlan Rawi Nasution; Mario Bagus Sanjaya; Nayla Khalisa; Harun Al-Rasyid (Universitas Maritim AMNI Semarang, 2025)
This study aims to analyze the study of as-saj’ in Surah Al-Ghasiyah, which is one of the surahs in the Qur'an that is rich in beautiful language. As-saj’, which means harmony of sound, plays an important role in increasing the appeal and understanding of the spiritual messages in this surah. This study uses a qualitative approach with a text analysis method, identifying various forms of as-saj’ found in Surah Al-Ghasiyah and how their use enriches the meaning of the verses. The results of the analysis show that there are several types of as-saj’, including saj’u mutawazi, saj’u mutarraf, and saj’u murasha’, each of which has its own characteristics and functions in creating rhythm and beauty of language. This study also found that the use of as-saj’ not only improves the linguistic aspect, but also deepens the reader's understanding of the moral and spiritual themes contained in the surah. Thus, this study makes a significant contribution to the study of linguistics and interpretation of the Qur'an, as well as increasing appreciation of the beauty of the Arabic language as divine revelation.